Analisis Capital Structure Terhadap Profitabilitas Perusahaan Property Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Maria Junianta; Darius Damestuteles; Fitria Elvi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The effect of capital structure on the profitability of the case study of property companies listed on the Indonesia Stock Exchange is the aim of this study for the 2019-2021 research period, the company's financial reports which become the data in this study are called secondary data. There were 29 samples in this study where the sample was selected based on the criteria of having complete financial report data during the study period. Analysis of financial report data produces a Debt to Equity Ratio (DER) variable that has a positive and significant effect on profitability.